2018
DOI: 10.1590/1516-4446-2017-2352
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and burden of mental health personnel: data from healthcare services for substance users and their families

Abstract: This study offers important information regarding the relationship of mental health personnel with their work. Care providers within this sample reported an overall high level of job satisfaction, while perceived burden differed by type of service and educational attainment. To our knowledge, this is the first study with a sample of mental health professionals working with substance users across five Brazilian states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…Si bien esta relación ha sido abordada por algunos estudios (33) , podrían del mismo modo existir otras variables que poseen un factor mediatizador, por ejemplo, la motivación y sentido intrínseco que un trabajador puede darle a su trabajo y contexto laboral.…”
Section: Discussionunclassified
“…Si bien esta relación ha sido abordada por algunos estudios (33) , podrían del mismo modo existir otras variables que poseen un factor mediatizador, por ejemplo, la motivación y sentido intrínseco que un trabajador puede darle a su trabajo y contexto laboral.…”
Section: Discussionunclassified
“…In addition to normal working hours, psychiatric nurses also need to undergo training, continuing education, and examinations, which often occupy their rest time and further increase their workload ( Jiang et al, 2019 ); for nurses, this results in lower satisfaction with training. Similarly, research in Brazil has shown that mental health workers are overloaded ( Hilgert et al, 2018 ). Therefore, the following problems should be considered in the improvement of training plans: a complete training infrastructure, sufficient time for training, and substantial practical guidance ( Mitchell et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fatores como altos níveis de estresse, menor satisfação no trabalho, aumento da rotatividade de pessoas, aumento do absenteísmo, menor produtividade e desgaste (afetando a saúde física, mental, desempenho no trabalho e a crescente intenção de parar com suas atividades) afetam o cuidado dos pacientes e de suas famílias 7 . Entender as relações entre os sujeitos e seu trabalho é uma preocupação para os pesquisadores, pois a satisfação no trabalho (ST) é um aspecto nesta relação que pode vir a influenciar a vida pessoal do trabalhador, interferindo seu comportamento em várias esferas da saúde 8 .…”
Section: Introductionunclassified